The Pocketable Electronic Devices in Radiation Oncology (PEDRO) Project: How the Use of Tools in Medical Decision Making is Changing?. (April 2016) - De Bari, Berardino; Franco, Pierfrancesco; Niyazi, Maximilian; Cornetto, Andrea Peruzzo; Qvortrup, Camilla; Martin, Arturo Navarro; Cacicedo, Jon; Fernandez, Gonçalo; Louro, Luís Vasco; Lestrade, Laëtitia; Ciammella, Patrizia; Greto, Daniela; et al.
Purpose: To analyze the impact of mobile electronic devices (MEDs) and apps in the daily clinical activity of young radiation or clinical oncologists in 5 Western European countries (Italy, Germany, Spain, Portugal, and Denmark). Methods: A web-based questionnaire was sent to 462 young (≤40 years) members of the national radiation or clinical oncology associations of the countries involved in the study. The 15 items investigated diffusion of MEDs (smartphones and/or tablets), their impact on daily clinical activity, and the differences perceived by participants along time. Results: A total of 386 (83.5%) of the 462 correctly filled questionnaires were statistically evaluated. Up to 65% of respondents declared to use an electronic device during their clinical activity. Conversely, 72% considered low to moderate impact of smartphones/tables on their daily practice. The daily use significantly increased from 2009 to 2012: users reporting a use ≥6 times/d raised from 5% to 39.9%. Professional needs fulfillment was declared by less than 68% of respondents and compliance to apps indications by 66%. Significant differences were seen among the countries, in particular concerning the feeling of usefulness of MEDs in the daily clinical life. The perception of the need of a comprehensive Web site containing a variety of applications (apps) for clinical use significantly differed among countries in 2009, while it was comparable in 2012. Conclusions: This survey showed a large diffusion of MEDs in young professionals working in radiation oncology. Looking at these data, it is important to verify the consistency of information found within apps, in order to avoid potential errors eventually detrimental for patients. "Quality assurance" criteria should be specifically developed for medical apps and a comprehensive Web site gathering all reliable applications and tools might be useful for daily clinical practice.